(untitled) (Revista jurídica latinoamericana, 2021)
Fecha de recepción, febrero 2020 Fecha de aprobación, noviembre 2020 Páginas: 6 The preventive detention or now called provisional detention has been throughout history one of the greatest evils of the Criminal Law; by means of the use of this merely instrumental measure our prisons, or subhuman dungeons have been throughout the years become saturated with inmates; either guilty or innocent. In this compendious, but substantial essay we intend to project that the deprivation of freedom under certain requirements should not become under any circumstance an anticipated punishment; considering the attacks that a person could suffer in a penitentiary center do not have atonement. Therefore, the judge, when deciding on the arguments of the parties, should demand a justified, proportional and suitable provisional detention or freedom under certain precautionary conditions.